2016
DOI: 10.1097/acm.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

Reflections From the Intersection of Health Professions Education and Clinical Practice: The State of the Science of Interprofessional Education and Collaborative Practice

Abstract: This informed reflection, from the intersection of health professions education and clinical practice, takes stock of the state of the field of interprofessional education (IPE) and collaborative practice (CP) (together IPECP) by answering the following three questions: (1) As a field of study, where is IPECP? (2) As a research enterprise, what are the current analytical gaps? (3) Scientifically, what needs to be done going forward? While IPE and CP, as well as IPECP, have been areas of scholarly inquiry for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Interprofessional education (IPE), defined as students from different health professions ‘learning with, from and about each other’ ( 16 ), is considered the basis of interprofessional practice and team-based care, a paradigm shift from the traditional hierarchical health care delivery model intended to improve the efficiency and quality of care ( 17 20 ). A recent position paper ( 21 ) on the intersection of IPE and collaborative practice stressed that IPE and team-based care are interconnected and that there is a need to apply educational best practices to patient care.…”
mentioning
confidence: 99%
“…Interprofessional education (IPE), defined as students from different health professions ‘learning with, from and about each other’ ( 16 ), is considered the basis of interprofessional practice and team-based care, a paradigm shift from the traditional hierarchical health care delivery model intended to improve the efficiency and quality of care ( 17 20 ). A recent position paper ( 21 ) on the intersection of IPE and collaborative practice stressed that IPE and team-based care are interconnected and that there is a need to apply educational best practices to patient care.…”
mentioning
confidence: 99%
“…Both surveys as well as research on interprofessional practice generally find that AHCs will need to become more inclusive of schools of nursing and other professional organizational partners and become more fully versed in evidence-based treatments if they are to effectively meet the needs of patients and adequately prepare the next generation of students. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 32 34 For instance, a 2013 Cochrane systematic review 35 covering 30 years of IPE research concluded that “it is not possible to draw generalizable inferences about the key elements of IPE and its effectiveness” on professional practice and health care outcomes. Similarly, a 2016 critical review 33 confirmed that the impact of IPE on health care was still awaiting scientific support. Moreover, a 2013 WHO report 23 found “no practice-level impact” on patient care and consequently recommended implementing IPE “only in the context of rigorous research.” This recommendation reversed the WHO’s earlier position on IPE.…”
Section: How and Why The Third Wave Of Ipe Is Falling Short Of Meetinmentioning
confidence: 99%
“…In their recent Academic Medicine article, Lutfiyya and colleagues 33 quoted John Gilbert’s response to the vexing question of whether IPE makes a difference to health care: “interprofessional education is a great truth awaiting scientific confirmation.” We take a different stance, suggesting that this “great truth” rests on too many shaky assumptions and flawed premises to justify continued practice and inquiry. Third wave advocates have made a compelling case for why we should focus on patient care and transform individuals to improve health care, yet we believe that continuing to look under the same proverbial lamppost (i.e., IPE) will not help us find the lost key to useful and effective education for collaboration.…”
Section: Wave 4: Addressing Workplace Systems and Structuresmentioning
confidence: 99%